Validating the ratio of insulin like growth factor binding protein 4 to sex hormone binding globulin as a prognostic predictor of preterm birth in Viet Nam: a case-cohort study - Hirst, JE; Boniface, JJ; Le, DP; Polpitiya, AD; Fox, AC; Vu, TTK; Dang, TT; Fleischer, TC; Bui, NTH; Hickok, DE; Kearney, PE; Thwaites, G; et al. (Taylor and Francis, 2024)
Objective To validate a serum biomarker developed in the USA for preterm birth (PTB) risk stratification in Viet Nam. Methods Women with singleton pregnancies (n = 5000) were recruited between 19+0-23+6 weeks’ gestation at Tu Du Hospital, Ho Chi Minh City. Maternal serum was collected from 19+0-22+6 weeks’ gestation and participants followed to neonatal discharge. Relative insulin-like growth factor binding protein 4 (IGFBP4) and sex hormone binding globulin (SHBG) abundances were measured by mass spectrometry and their ratio compared between PTB cases and term controls. Discrimination (area under the receiver operating characteristic curve, AUC) and calibration for PTB <37 and <34 weeks’ gestation were tested, with model tuning using clinical factors. Measured outcomes included all PTBs (any birth ≤37 weeks’ gestation) and spontaneous PTBs (birth ≤37 weeks’ gestation with clinical signs of initiation of parturition). Results Complete data were available for 4984 (99.7%) individuals. The cohort PTB rate was 6.7% (n = 335). We observed an inverse association between the IGFBP4/SHBG ratio and gestational age at birth (p = 0.017; AUC 0.60 [95% CI, 0.53-0.68]). Including previous PTB (for multiparous women) or prior miscarriage (for primiparous women) improved performance (AUC 0.65 and 0.70, respectively, for PTB <37 and <34 weeks’ gestation). Optimal performance (AUC 0.74) was seen within 19-20 weeks’ gestation, for BMI >21 kg/m2 and age 20-35 years. Conclusion We have validated a novel serum biomarker for PTB risk stratification in a very different setting to the original study. Further research is required to determine appropriate ratio thresholds based on the prevalence of risk factors and the availability of resources and preventative therapies.